Alcohol and the liver. (November 2019) - Chaudhary, Sardar; Forrest, Ewan H.
Abstract: Hospital admissions because of alcohol-related liver disease (ArLD) are increasing. The amount of alcohol consumed and pattern of drinking are linked to increased risk of ArLD. However, other factors such as obesity, co-existent liver disease – particularly hepatitis C, gender, nutritional status and genetic factors also play a role. The spectrum of ArLD ranges from steatosis to alcoholic hepatitis to established cirrhosis, and the alcohol-related injury involves multiple mechanisms. Chronic, excessive alcohol consumption can cause cirrhosis in the absence of alcohol dependency syndrome or indicators of alcohol abuse. Presentation is variable, and recognition requires the clinician to be aware of the significance of a history of alcohol excess, clinical stigmata of liver disease and compatible laboratory investigations. Not all people who drink excess alcohol have alcohol as the cause of their liver disease, and other aetiologies must be excluded. The key to management is long-term abstinence, and interventions should be delivered in conjunction with addiction services. Nutritional issues should also be addressed. Acute alcoholic hepatitis has a high mortality, and patients with the highest risk can benefit from short-term corticosteroids. Cirrhotic patients require hepatoma surveillance and variceal screening; liver transplant should be considered in selected cases.